Examining Call for the Dissolution of Indonesian Ulema Council: Siyāsah Syar’íyyah Perspective - Abdul Syatar; Muhammad Imran; M Ilham; Kurniati Kurniati; Marilang Marilang; Kamaluddin Nurdin Marjuni (JURIS (Jurnal Ilmiah Syariah), 2023)
The religious authoritative institution of the Indonesian Ulema Council (MUI), is facing infiltration by members connected with acts of terrorism. This leads to public demands for its dissolution under the banner of "Joint Enemy Terrorism". Therefore, this study aimed to assess the possibility of dissolving MUI by reviewing the root causes of terrorism within the religious institution. Through the lens of Islamic political analysis and a critical examination of various data sources, it became evident that the discourse advocating for the dissolution centered around the hashtag #BubarkanMUI#. This hashtag campaign was initiated to frame the participation of MUI members in extremist activities, thereby posing a threat of criminal terrorism. MUI, on the other hand, was beyond dispute due to its strong and legally entrenched position. In this context, the prospect of the dissolution became irrelevant, impractical, and challenging to materialize primarily due to membership issues. The existence of MUI was strengthened and secured through several laws mandating its engagement, including the certification of halal products and regulation of Sharia banking. This showed the religious institution must embark on a thorough evaluation and enhancement of both its structural framework and membership recruitment processes. Regarding the authority to dissolve non-political institutions and organizations, this prerogative should be entrusted to the Constitutional Court, serving as a judicial entity responsible for safeguarding democracy, human rights, and constitutional principles.